SYT6 protein role in Arabidopsis thaliana contact sites. - Moya-Barrientos, Miriam; Huércano Rubens, Carolina; Morello-López, Jorge; Cardeñas Echevarría, Carlos; Boutté, Yohann; Sánchez-Vera, Victoria; Ruiz-López, Noemí (My University, 2024)
The SYT6 protein from A. thaliana (AT3G18370) has recently been identified as a lipid transfer protein localized at membrane contact sites (MCS). MCS are regions where membranes of two organelles closely approach without membrane fusing, typically within 10-30 nm [1]. Historically, research has primarily focused on endoplasmic reticulum (ER) and plasma membrane (PM) MCS [2], but recently MCS involving the ER and other organelles have come to light. SYT6 is a plant exclusive protein exhibiting a modular structure shared with mammalian Extended-Synaptotagmins (E-SYTs) and other plant synaptotagmins, such as SYT1. Our ongoing experiments suggest that SYT6 anchors itself to the ER via its transmembrane domain (TM), contains a lipid trafficking domain (named SMP) [3] and attaches to specific trans-Golgi Network (TGN) vesicles through its C2 domains and coiled-coil domain. These observations make SYT6 a particularly intriguing protein, given that its physiological roles remain unclear. Currently, our focus lies in studying SYT6 to uncover its expression, subcellular localization and most importantly, its function. Thanks to confocal imaging, we have confirmed SYT6 attachment to the ER and to big and small vesicles in continuous motion, suggesting its involvement in secretory trafficking. These findings, combined with Co-Immunoprecipitation experiments, have confirmed the interaction between SYT6 and specific TGN proteins linked to the independent Golgi TGN (GI-TGN). Moreover, our preliminary findings have showed a correlation between SYT6, exocytosis and autophagy. Furthermore, it has been observed that syt6 mutant exhibits distinct phenotypic traits compared to the wild-type, notably displaying altered negative gravitropism. Altogether, these findings suggest that SYT6 represents a novel ER-TGN CS protein that may play a role in secretory trafficking.
Keywords: Arabidopsis thaliana - Citología; Proteínas vegetales; SYT6; Contact sites; Endoplasmic reticulum; Trans golgi network